Resources, values and development - Sen, Amartya (New Delhi, 2012)
This volume contains many of Amartya Sen's most important contributions to economic analysis and methods, including papers on resource allocation in nonwage systems, investments planning, shadow pricing, employment policy, and welfare economics.
Keywords: "Economic development, Social values, Welfare economic"